Quantifying the effect of labor market size on learning externalities - Jan Cornelius Peters (European Regional Science Association (ERSA), 2016)
It is well known that wages in large cities are higher than elsewhere. There is only little empirical evidence on the mechanisms behind this phenomena. One channel, that is discussed in the literature, is learning. Provided that individuals learn by interacting with one another, an urban wage growth premium arises if a large labor market increases the speed of interactions between individuals (Glaeser, 1999). To analyze dynamic agglomeration benefits and the importance of learning effects, this paper makes use of a micro econometric framework described by Combes and Gobillon (2015), extents the work by De la Roca and Puga (2013) and, in contrast to previous papers, provides a consistent estimate of the elasticity between wages and the size of the labor market where experience was acquired. The analyzed wages refer to new employment relationships. They indicate how firms value working experience depending on the location where it was acquired. By including fixed effects and further control variables at both, the individual as well as the regional level, endogeneity is reduced. The paper also analyzes whether the value of experience depends not only on the size of the labor market where experience was acquired, but also on the size of the labor market where it is used. The analysis bases on a 5 percent sample of the Integrated Employment Biographies (IEB) of the Institute for Employment Research (IAB) and contains detailed information on the employment biographies from 1975 onwards for a sample of about 350,000 individuals with at least one new employment relationship in Germany between 2005 and 2011. The results indicate that experience acquired in large local labor markets has in fact a significantly higher valued than experience acquired in small labor markets. The elasticity has a fixed component and a component that depends on the size of the labor market where experience is used. The fixed component (about 0.07) points out, that experience acquired in large labor markets is in all regions valued higher than experience acquired in small labor markets. This supports the interpretation that workers learn more by working in large than in small labor markets, and that at least part of the accumulated knowledge are transferable to other regions. The second component suggests that the value of experience increases additionally with the size of the labor market where experience is used. One reasonable explanation is a combination of learning and matching effects. Since jobs in large labor markets are more specialized than jobs elsewhere, workers that worked in a large labor market accumulated knowledge that refers to the 'core task' of a job. The wage premium for this knowledge is supposed to be larger in large labor markets, since it is more likely there than in a smaller labor market, that a firm demands this specific knowledge. Moreover, workers moving from a large to a small labor market may lose since the new job contains a wider range of tasks.
Keywords: R23; J31; 330; Agglomeration economies; Learning; Urban wage growth premium; Transition to employment